Soil conservation strategies for upland areas of Indonesia - Carson, Brian (East-West Environment and Policy Institute, 1989)
This book summarizes the work author has carried out on the use of maps and aerial photographs in RRA of watershed issues with KEPAS (Agroecosystems Research Group within the Ministry of Agriculture, Indonesia) between 1986 and 1988. Key for watershed planners